The women's soccer health study: from head to toe - Ling, D. I.; Hannafin, J. A.; Prather, H.; Skolnik, H.; Chiaia, T. A.; de Mille, P.; Lewis, C. L.; Casey, E. (Sports Medicine, 2023)
Objectives: Women are under-represented in the sports literature despite increasing rates of sports participation. Our objective was to investigate the risks and benefits of an elite women`s soccer career in five health domains: general, musculoskeletal, reproductive endocrinology, post-concussion, and mental. Methods: An online survey was distributed to retired US college, semi-professional, professional, and national team soccer players using personal networks, email, and social media. Short validated questionnaires were used to evaluate the health domains, including the Patient-Reported Outcomes Measurement Information System (PROMIS), Single Assessment Numerical Evaluation (SANE), Post-Concussion Symptom Scale (PCSS), and Patient Health Questionnaire (PHQ). Results: A total of 560 eligible players responded to the survey over a 1-year period. The highest competitive levels were 73% college, 16% semi-professional, 8% professional, and 4% national team. The mean number of years since retirement was 12 (SD = 9), and 17.0% retired for involuntary reasons. The mean SANE scores (0-100 scale as percentage of normal) were knee = 75% (SD = 23), hip = 83% (SD = 23), and shoulder = 87% (SD = 21). The majority (63%) reported that their current activity level included participation in impact sports. A substantial proportion of players reported menstrual irregularities during their careers: 40% had fewer periods with increasing exercise and 22% had no periods for = 3 months. The players (n = 44) who felt that post-concussion symptoms were due to soccer reported more time-loss concussions (F[2] = 6.80, p = 0.002) and symptom severity (F[2] = 30.26, p < 0.0001). Players who recently retired (0-5 years) reported the highest anxiety/depression scores and lowest satisfaction rates compared with those who retired 19+ years ago. Conclusion: Health concerns include musculoskeletal injuries, post-concussion symptoms, and lower mental health in the early years following retirement. This comprehensive survey provides initial results that will lay the foundation for further analyses and prioritize research studies that can help all female athletes.